Mutualistic interactions facilitating Ulex europaeus invasion in southern Brazil and its potential disruption of local ecosystems - Matheus Vinicius Kirsch Renck; Diego Hoffmann; Francielle Paulina de Araújo-Hoffmann (Acta Botânica Brasílica)
Abstract This study investigates the role of mutualistic interactions in facilitating the invasion of Ulex europaeus (Fabaceae) in the southern Brazilian highland grasslands. We assessed its reproductive phenology, floral resources, pollinator interactions, and seed dispersal mechanisms. Observations revealed that U. europaeus flowers predominantly during winter, with peak flowering occurring in August. During this period, no native species were in bloom, and Apis mellifera was the sole pollinator observed. Pollen analysis showed that honeybees carried U. europaeus pollen almost exclusively in winter, but diversified their loads in spring when other species began flowering. We also confirmed seed dispersal by native ant species, although grazing animals did not contribute to seed dispersal. Our findings suggest that the successful invasion of U. europaeus is enhanced by its interaction with A. mellifera, a species with which it co-evolved in its native range, despite limited interaction with native pollinators. Additionally, seed dispersal by native ants further contributes to its spread. These mutualistic relationships, especially with A. mellifera, play a significant role in the species' spread and dominance, potentially threatening local biodiversity. Understanding these ecological interactions is crucial for developing strategies to control the spread of U. europaeus and mitigate its impacts on native ecosystems.